Scope of Solar Energy in Cold Arid Region of India at Leh Ladakh - Santra, Priyabrata (Annals of Arid Zone, 2016)
Considering the fast depletion of fossil fuel, there is need for switching to renewable options for meeting the energy demands in future e.g. solar, wind, biomass etc. At present, 13% of the electricity production in our country is met through renewable sources, whereas globally it is about 22.8%. If we think about the availability of solar irradiation in India, it is abundantly available in cold arid regions at Leh-Ladakh. In spite of large availability of solar irradiation at Leh-Ladakh, e.g. 7-7.5 kWh m-2 day-1, huge amount of diesel is still being used for meeting the daily energy demands of Leh-Ladakh. Solar energy has a great role to play for future energy security of Leh and Ladakh either through solar thermal or solar photovoltaic options. In this paper, different solar based technologies are discussed to use solar energy at domestic level, at farmers’ field and even at industrial scale. Solar PV pumping system can easily be used for irrigation purpose and even to lift water against gravity at undulating terrains of Leh-Ladakh. Solar farming option can be utilized where both crop production and PV based electricity generation can be done on a single land use system. Solar air heating for buildings may provide congenial inside environment especially during winter months. Solar green house can be an effective way to produce vegetables even during harsh climatic conditions outside. Roof top PV system can share the electric energy consumptions in office buildings, hospitals, guest houses, hotels etc. Solar lanterns have the potential to replace conventionally used kerosene based lighting system. Other different solar technologies that have a potential in Leh-Ladakh are inclined solar dryer, solar PV winnower cum dryer, solar water heater etc. Utilization of above discussed solar based technologies may have improved the renewable energy scenario in Leh and Ladakh. Key words: Renewable energy, Leh and Ladakh, solar thermal devices, solar PV technologies.